PEMBELAJARAN FISIKA DENGAN GAME ANGRY BIRDPADA MATERI GERAK TERHADAP PEMAHAMAN KONSEP SISWA SMA - Nira Nurwulandari; Lidana Marta Sitika (Universitas Muhammadiyah Semarang, 2018)
Students experience difficulties in learning physics because of low understanding of concepts. Fun learning is expected to improve understanding of concepts, one of which is with Angry Bird games. In Angry Bird games students can learn parabolic motion material. This study aims to determine the effect of the use of Angry Bird games on understanding the concept of physics in parabolic motion material.This study uses a mixed method approach with embedded design. The study was conducted in class X with a research subject of 33 students. Qualitative data in the form of concept understanding obtained from LKS results, quizzes, post-test pre-tests and interview results are then analyzed through data collection, reduction, coding, presentation and conclusion. Quantitative data were analyzed through percentage, mean, and paired t-tests.Research shows that: 1) There is an effect of using Angry Bird games onunderstanding students' physics concepts. This is shown through the quiz results obtained an average score of 73.57%. In addition, the LKS results obtained an average score of 80.7%. 2) Understanding students' physics concepts changes after learning with Angry Bird games. This result is also supported by the results of the paired t-test analysis which shows that the densest difference between the average score of understanding students' physics concepts in the pre-test and post-test. Keywords: angry bird, parabolic motion, concept understanding